ANALISIS PENGARUH BUDAYA ORGANISASI DAN KEPUASAN KERJA TERHADAP KOMITMEN ORGANISASIONAL DALAM MENINGKATKAN KINERJA KARYAWAN (Studi pada PT. Sido Muncul Kaligawe Semarang) - Melina Taurisa, Chaterina; Ratnawati Intan (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2012)
The purpose of this study is to analyze the influence of organizational culture, job satisfaction, and organizational commitmenton employee performance. The object of research in this study is PT. Sido Muncul Kaligawe Semarang. Data are collectedthrough self administered questionnaire completed by 127 respondents with census method and the model is tested throughStructural Equation Modeling (SEM). The measurement of exogenous and endogenous constructs are tested usingconfirmatory factor analysis, and the result shows that the Goodness-of-Fit test of full model is in the range of expected values.The findings of this study prove and give conclusions as following: (1) organizational culture has positive and significant effecton job satisfaction, (2) organizational culture has positive and significant effect on organizational commitment, (3) jobsatisfaction has positive and significant effect on organizational commitment, (4) organizational commitment has positive andsignificant effect on employee performance, (5) organizational culture has positive and significant effect on employeeperformance, and (6) job satisfaction has positive and significant effect on employee performance.Key words: organizational culture, job satisfaction, commitment organizational, and employee performance.